2016
DOI: 10.1038/ejhg.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

Genetic investigation of 100 heart genes in sudden unexplained death victims in a forensic setting

Abstract: In forensic medicine, one-third of the sudden deaths remain unexplained after medico-legal autopsy. A major proportion of these sudden unexplained deaths (SUD) are considered to be caused by inherited cardiac diseases. Sudden cardiac death (SCD) may be the first manifestation of these diseases. The purpose of this study was to explore the yield of next-generation sequencing of genes associated with SCD in a cohort of SUD victims. We investigated 100 genes associated with cardiac diseases in 61 young (1-50 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 53 publications
1
38
0
5
Order By: Relevance
“…Cardiac channelopathy and cardiomyopathy have been widely recognized as causes of deaths in individuals who died suddenly in a natural manner (Fernandez-Falgueras, Sarquella-Brugada, Brugada, Brugada, & Campuzano, 2017;Magi, Lariccia, Maiolino, Amoroso, & Gratteri, 2017). Studies have shown that 13%-41% of the time, a pathogenic or likely pathogenic genetic change can be identified through postmortem genetic testing in SD, which is consistent with a NAME position statement that suggests this number could be up to 40% (Campuzano et al, 2014;Christiansen et al, 2016;Lahrouchi et al, 2017;Middleton et al, 2013;Stattin et al, 2016;Tester, Medeiros-Domingo, Will, Haglund, & Ackerman, 2012). Two separate studies found that a clinical diagnosis was established in family members of a decedent with a pathogenic variant in a cardiac gene approximately 12%-13% of the time (Bagnall et al, 2016;Lahrouchi et al, 2017).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Cardiac channelopathy and cardiomyopathy have been widely recognized as causes of deaths in individuals who died suddenly in a natural manner (Fernandez-Falgueras, Sarquella-Brugada, Brugada, Brugada, & Campuzano, 2017;Magi, Lariccia, Maiolino, Amoroso, & Gratteri, 2017). Studies have shown that 13%-41% of the time, a pathogenic or likely pathogenic genetic change can be identified through postmortem genetic testing in SD, which is consistent with a NAME position statement that suggests this number could be up to 40% (Campuzano et al, 2014;Christiansen et al, 2016;Lahrouchi et al, 2017;Middleton et al, 2013;Stattin et al, 2016;Tester, Medeiros-Domingo, Will, Haglund, & Ackerman, 2012). Two separate studies found that a clinical diagnosis was established in family members of a decedent with a pathogenic variant in a cardiac gene approximately 12%-13% of the time (Bagnall et al, 2016;Lahrouchi et al, 2017).…”
Section: Introductionsupporting
confidence: 63%
“…The yield, or percentage of positive cases, of 10.6% is markedly lower than other cohorts which have described yields upwards of 40% (Campuzano et al, 2014;Christiansen et al, 2016;Lahrouchi et al, 2017;Middleton et al, 2013;Stattin et al, 2016;Tester et al, 2012). This could be due to the inclusion of genes associated with both channelopathies and cardiomyopathies, for all SD cases deemed necessary for testing by medical examiners, versus stringent inclusion criteria and more targeted panels.…”
Section: Practice Implications and Research Recommendationsmentioning
confidence: 76%
“…Post-mortem genetic studies have shown that SCD in these victims can be caused by fatal arrhythmias secondary to a group of inheritable cardiac electrical disorders collectively known as sudden arrhythmia death syndrome (SADS). [10][11][12][13][14] These include Brugada syndrome (BrS), long QT syndrome (LQTS), short QT syndrome, catecholaminergic polymorphic ventricular tachycardia (CPVT), arrhythmogenic right ventricular cardiomyopathy (ARVC), hypertrophic cardiomyopathy (HCM), and other cardiomyopathies.…”
Section: Introductionmentioning
confidence: 99%
“…Bu da bu vakalarda yaştan bağımsız bir şekilde ayrıntılı genetik incelemenin yapılmasını tanısal bilgimizin artması perspektifinden destekler niteliktedir. (9) 10318 hastanın katıldığı bir meta-analizde 261 tesadüfi AKÖ vakası değerlendirilmiş (ortalama takip süresi 9,1 yıl) ve yüksek serbest T4 seviyelerinin tiroid fonksiyonu normal olsa bile artmış AKÖ riski ile ilişkili olduğu gösterilmiştir. Yaş, cinsiyet ve duyarlılık analizlerinde yapılan düzeltmelerle de riskte anlamlı bir değişim olmamıştır.…”
Section: Akö Nedenleriunclassified